2011
DOI: 10.1002/jmv.22234
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of arbidol, a broad‐spectrum drug for use against respiratory viruses, varies according to test conditions

Abstract: The therapeutic activity of arbidol was investigated against representatives of seven different virus families. Its 50% median effective concentration (EC(50) ) was 0.22-11.8 µg/ml (0.41-22 nM). Therapeutic indices of 91 were obtained for type 1 poliovirus and 1.9-8.5 for influenza A and B, human paramyxo-3, avian infectious bronchitis-, and Marek's disease viruses. Arbidol was more inhibitory for influenza A/Aichi/2/68 (H3N2) virus than rimantadine or amantadine (EC(50) 10 vs. >15 and >31.6 µg/ml); greater in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(89 citation statements)
references
References 38 publications
3
77
0
9
Order By: Relevance
“…Previous in vitro and in vivo studies have shown that Arbidol has broad-spectrum activity against influenza viruses (16)(17)(18)21). Comparison of the Arbidol-binding site in group 2 HAs against the corresponding region in group 1 HA [H1N1 A/Puerto Rico/8/1934 (H1/PR8; PDB ID code 1RU7)] reveals important structural differences between the two groups ( Fig.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous in vitro and in vivo studies have shown that Arbidol has broad-spectrum activity against influenza viruses (16)(17)(18)21). Comparison of the Arbidol-binding site in group 2 HAs against the corresponding region in group 1 HA [H1N1 A/Puerto Rico/8/1934 (H1/PR8; PDB ID code 1RU7)] reveals important structural differences between the two groups ( Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Arbidol (umifenovir) is a broad-spectrum antiviral against a number of enveloped and nonenveloped viruses such as influenza, respiratory syncytial (RSV), adenovirus, Coxsackie B5, parainfluenza, Ebola (EBOV), and hepatitis B and C (14)(15)(16)(17)(18)(19)(20). Arbidol demonstrates broad activity against diverse strains and subtypes of influenza A and B viruses and is effective in mice infected with A/California/07/2009 (H1N1), A/Puerto Rico/8/1934 Significance Influenza virus is an important human pathogen.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Противовирусная активность умифеновира in vitro и in vivo выявлена в отношении различных вирусов, в част-ности вирусов гриппа А и В, включая сезонные и высоко-патогенные подтипы A(H1N1)pdm09 и A(H5N1), ряда других возбудителей ОРВИ (аденовирус, респираторно-синцитиальный вирус, коронавирус, или вирус атипич-ной пневмонии -ТОРС, риновирус, вирус парагриппа) [22][23][24][25].…”
Section: контактная информацияunclassified
“…Arbidol (or umifenovir) (1-methyl-2-phenylthiomethyl-3-carbethoxy-4-dimetylaminomethyl-5-hydroxy-6-bromoindole) is a Russian-made indole-derivative molecule with antiviral activity [10,11] and immunomodulatory effect ( Figure 1) [12,13]. Arbidol activity results from its ability to inhibit fusion of a virus lipid envelope with endosome membranes located within the cell.…”
Section: Introductionmentioning
confidence: 99%